2004
DOI: 10.1056/nejmoa030107
|View full text |Cite
|
Sign up to set email alerts
|

Persistent GB Virus C Infection and Survival in HIV-Infected Men

Abstract: GBV-C viremia was significantly associated with prolonged survival among HIV-positive men 5 to 6 years after HIV seroconversion, but not at 12 to 18 months, and the loss of GBV-C RNA by 5 to 6 years after HIV seroconversion was associated with the poorest prognosis. Understanding the mechanisms of interaction between GBV-C and HIV may provide insight into the progression of HIV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
268
2
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(293 citation statements)
references
References 38 publications
19
268
2
4
Order By: Relevance
“…In this study, a similar prevalence of antibody (22.5%) and RNA (25.3%) was observed, resembling what has been described in other groups of individuals with impaired immunity, which may be ascribed to a lower clearance rate, when compared with immunocompetent populations where a rate of viremia to antibody of 1:6 is generally observed 23 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, a similar prevalence of antibody (22.5%) and RNA (25.3%) was observed, resembling what has been described in other groups of individuals with impaired immunity, which may be ascribed to a lower clearance rate, when compared with immunocompetent populations where a rate of viremia to antibody of 1:6 is generally observed 23 .…”
Section: Discussionsupporting
confidence: 89%
“…Several studies corroborated these findings 23 while a few others failed to substantiate them 22 . More recently, a meta-analysis has tried to summarize most of the experimental data regarding this issue and concluded that GBV-C does exert a protective effect in the evolution to AIDS in HIV-infected individuals, independent of several potential confounders 26 .…”
Section: Introductionmentioning
confidence: 96%
“…A B [3][4][5][15][16]. Both direct interference on HIV-l replication, such as inhibition ofHIV-I entry in target cells mediated by down-regulated CCR5 co-receptor expression (9,17), and indirect mechanisms, such as prolonged maintenance of an intact Thl cytokine profile (10) and an increased number of circulating "(8 T cells releasing antiviral cytokines (18)(19), have been proposed.…”
Section: Experiment) the Maturation State Ofdc Was Evaluated Using Amentioning
confidence: 99%
“…However, the pathogenic relevance of GBV-C, if any, remains unclear. It does not cause hepatitis but has been associated with prolonged survival in human immunodeficiency virus-infected individuals (62)(63)(64). Bovine viral diarrhea virus (BVDV) is the prototype pestivirus.…”
mentioning
confidence: 99%